Management Accounting in Indonesia: Analysis of Current Systems, Potential for Change and Forces behind Innovation - Jermias, Johny; Armitage, Howard M (Accounting Department,, 2000)
The paper begins with a- description of the current practice of management accounting in Indonesia and the degree to which management accounting systems and management accountants are expected to change during the next ï¬ve years. This is followed by an empirical examination of the relationship between management accounting innovation in lndonesia and such factors as organization hierarchy, system design, company performance, size, and age. As predicted, results from this study indicated that the level of management accounting system innovation can be predicted by the level of hierarchy and the nature of organizational design. Increased hierarchy has a negative association with innovation in management accounting systems. Similarly, organizations that are process oriented use more innovative management accounting systems than functionally oriented organization. Key words: innovation, management accounting, hierarchy, lndonesia.